PENGARUH PENGGUNAAN MEDIA BLOK PECAHAN TERHADAP KEMAMPUAN BERHITUNG SISWA PADA MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN KELAS IV UPT SDN 18 TURATEA - Lestari, Alisa; Rahmawati Patta; Hardianto Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to (1) describe the application of fraction block media on the addition and subtraction of fractions material in class IV UPT SDN 18 Turatea, (2) find out the description of students' arithmetic ability using fraction block media, and (3) find out the effect of fraction block media on students' arithmetic ability on the addition and subtraction of fractions material. This study is included in the category of experimental research with a quantitative approach and uses pre-experimental design research (nondesigns) with a one sample pretest-posttest type. The population of this study was all students of class IV UPT SDN 18 Turatea, with a sample of 19 students selected through saturated sampling techniques. Data were collected using observation sheets to determine the implementation of fraction block media, student arithmetic ability tests and documentation. Data analysis was carried out descriptively and inferentially. The results of the descriptive analysis showed that the implementation of the learning process using fraction block media was in the good category at the first meeting and very good at the second meeting. While for students, the percentage of the implementation of the learning process at both meetings was included in the very good category. Inferential analysis using paired sample t-test showed a significant difference between the pretest and posttest results. This indicates an increase in students' arithmetic ability after being given treatment. Thus, it can be concluded that: (1) the learning process using fractional block media runs very well, (2) The description of students' arithmetic ability shows an increase after using fractional block media, shown from the results of the posttest which is higher than the pretest and (3) there is an influence of the use of fractional block media on students' arithmetic ability on the addition and subtraction of fractions material for class IV UPT SDN 18 Turatea.